Was ist x, wenn ln (x ^ 2) + ln (x ^ 3) + 2 = 0 ist?

Was ist x, wenn ln (x ^ 2) + ln (x ^ 3) + 2 = 0 ist?
Anonim

Antworten:

# x = Wurzel (5) (1 / e ^ 2) #

Erläuterung:

# 1 "" lnx ^ 2 + lnx ^ 3 + 2 = 0 #

Eigentum: # log_bm + log_bn = log_b (mn) #

# 2 "" ln (x ^ 2x ^ 3) + 2 = 0 #

# 3 "" ln (x ^ 5) + 2 = 0 #

Übertragen Sie 2 auf die andere Seite.

# 4 "" ln (x ^ 5) = - 2 #

# 5 "" log_e (x ^ 5) = - 2 #

In exponentielle Form konvertieren.

# 6 "" hArre ^ -2 = x ^ 5 #

# 7 "" root (5) (1 / e ^ 2) = root (5) (x ^ 5) #

# 8 "" Farbe (blau) (x = Wurzel (5) (1 / e ^ 2)) #